2015
DOI: 10.1016/j.ultsonch.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cell membrane damage induced by the therapeutic ultrasound on human breast cancer MCF-7 and MCF-7/ADR cells

Abstract: Ultrasound exposure decreased MCF-7 and MCF-7/ADR cell viability in an intensity-dependent manner and MCF-7/ADR cells were more sensitive to ultrasound exposure than MCF-7 cells at the same experimental conditions. The declined membrane fluidity in MCF-7/ADR cell may be one of the reasons for its increased membrane damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Secondly, based on our results, higher potential values of sonoporation are suggested for drug-resistant tumor cells, as the sonoporation efficiency of the MCF-7/ADR cell line was higher than that of the MCF-7 cell line. This reflects the higher sensitivity to enhanced sonoporation mediated by USMB exposure for MCF-7/ADR cells than MCF-7 cells, which is consistent with a previous study [31]. The underlying mechanism might involve the enhancement of cell membrane permeability and downregulation of MDR-related genes and proteins [32].…”
Section: Discussionsupporting
confidence: 88%
“…Secondly, based on our results, higher potential values of sonoporation are suggested for drug-resistant tumor cells, as the sonoporation efficiency of the MCF-7/ADR cell line was higher than that of the MCF-7 cell line. This reflects the higher sensitivity to enhanced sonoporation mediated by USMB exposure for MCF-7/ADR cells than MCF-7 cells, which is consistent with a previous study [31]. The underlying mechanism might involve the enhancement of cell membrane permeability and downregulation of MDR-related genes and proteins [32].…”
Section: Discussionsupporting
confidence: 88%
“…Ultrasound is known to promote membrane permeability, thus increasing intracellular drug accumulation. Previous studies have suggested that the mechanisms by which ultrasound enhances the cytotoxicity of chemotherapy drugs include increased generation of reactive oxygen species [10,11], intracellular drug accumulation [12,13], and cell membrane permeability [14,15,16]. The combined therapy concentration and sufficient exposure time were crucial to the chemotherapeutic efficacy in our study.…”
Section: Discussionmentioning
confidence: 55%
“…Intracellular ROS plays an important role in SDT . It has been reported that Cu–Cy nanoparticles can generate a large amount of ROS when irradiated by X‐ray or microwave .…”
Section: Resultsmentioning
confidence: 99%
“…For Control and US group, cells were incubated by equal complete culture medium at 37 °C for 24 h. US and SDT groups cell were then exposed to ultrasound treatment. For the in vitro ultrasound set‐up, a planar transducer was used as previously described and 0.5 W cm −2 with duty cycle of 20%, duration of 60 s was used for ultrasound treatment.…”
Section: Methodsmentioning
confidence: 99%